The Mediating Role of Information Technology, Internal Control System on the relationship between Human Resources Competence and Manokwari Regency Local Government Financial Statements - simson, werimon (Universitas Cenderawasih, 2025)
Abstract The purpose of the study was to examine the effect of Human Resources Competence (HRC), on the Quality of Local Government Financial Statements through the Utilization of Information Technology (IT) and Internal Control System (ICC) as mediating variables. The data were analyzed using the Structural Equation Modeling approach with Partial Least Square (SEM-PLS), the research subjects were Civil Servants, the number of samples was 75. The results prove that KSDM has no direct effect on LKPD with a p value of (0.087> 0.05) and in a 97.5% confidence interval of 32.3% the influence of KSDM on improving the quality of LKPD. In the PTI and SPI mediation test, these two variables are able to mediate HRD with LKPD and P-Value = (0.013 - 0.015 <0.05) and have a positive and significant effect on LKDP, in the 97.5% confidence interval the influence of PTI and SPI values in mediating HRD with LKPD lies between 27.1%-44.2%, with a mediation path coefficient of (0.160-0.252) and significant with t statistics (2.425 - 2.747> 1.96), Although the results are influential but have a low effect, this is supported by the output of the calculation of the effect size value of mediation ranging from 0.03-0.06, and these results are still reinforced by the results of the Q2 test which proves that the Q2 value is at 0.15-0.29 still in the category of relevant prediction power, meaning that any changes in the Quality of Local Government Financial Statements can be predicted by PTI and SPI variables as mediating variables Keywords: Human Resources Competence, Information Technology, Internal Control System, Mediation.